Measurement of the top quark mass in the lepton+jets final state with the matrix element method - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Society (APS), 2006)
We present a measurement of the top quark mass with the matrix element method in the lepton+jets final state. As the energy scale for calorimeter jets represents the dominant source of systematic uncertainty, the matrix element likelihood is extended by an additional parameter, which is defined as a global multiplicative factor applied to the standard energy scale. The top quark mass is obtained from a fit that yields the combined statistical and systematic jet energy scale uncertainty. Using a data set of 0.4fb-1 taken with the D0 experiment at Run II of the Fermilab Tevatron Collider, the mass of the top quark is measured using topological information to be: mtopℓ+jets(topo)=169. 2-7.4+5.0(stat+JES)-1.4+1.5(syst)GeV, and when information about identified b jets is included: mtopℓ+jets(b-tag)=170.3-4.5+4.1(stat+JES)-1.8+1.2(syst) GeV. The measurements yield a jet energy scale consistent with the reference scale. © 2006 The American Physical Society.